Does the marketization of land transfer have an impact on carbon emissions? Evidence from China - Zhang, Ruigang; Yang, Runze; Huang, Yu (Frontiers in Environmental Science, 2022)
Excessive carbon emissions caused by extensive economic development is the key to the current government's carbon emission reduction goals. In the process of market-oriented reform of land transfer, alleviating the contradiction between land use and low-carbon development is an important problem to achieve the goal of carbon peaking and carbon neutrality. The impact of land transfer marketization on regional economic development is complex, and the final impact on carbon emissions needs to be further examined. Based on China's provincial panel data from 2008 to 2017, this paper uses a double fixed effect model to conduct an empirical analysis. The lag effect of the initial regression results is tested, and the quantitative test of the mediating effect and moderating effect of fixed asset investment is also carried out. The following conclusions are drawn: Firstly, the improvement of the marketization of land transfer will promote carbon emissions; secondly, the promotion effect of the degree of marketization of land transfer on carbon emissions will become inhibited with the delay of the lag effect years. Moreover, fixed asset investment will play a masking effect and an adjustment effect; thirdly, the impact of the degree of marketization of land transfer on carbon emissions is different in the eastern and western regions divided by the degree of marketization, and the strength of government control will also have a significant impact on the impact. The research results of this paper enrich the economic impact theory of land transfer marketization, and have certain value for regional land policy management in the context of carbon emission reduction.